Aqueous Nyctanthes arbortristis and doxorubicin conjugated gold nanoparticles synergistically induced mTOR-dependent autophagy-mediated ferritinophagy in paclitaxel-resistant breast cancer stem cells - Chittineedi, Prasanthi; Pandrangi, Santhi Latha; Neira Mosquera, Juan Alejandro; Sánchez Llaguno, Sungey Naynee; Mohiddin, Gooty Jaffer (Frontiers in Pharmacology, 2023)
Nyctanthes arbortristis Linn is a potential anti-diabetic drug that reduces glucose levels by delaying carbohydrate digestion. The tumor microenvironment is characterized by elevated glucose levels that activate various genes, such as mTOR. mTOR plays a critical role in maintaining the hypoxic environment and inhibiting autophagy. Although natural compounds pose fewer side effects, their hydrophobic nature makes these compounds not suitable as therapeutics. Hence, we conjugated aqueous NAT into gold nanoparticles (AuNP) in the current study and evaluated the ability of the chosen drugs to induce cell death in breast cancer cells resistant to Paclitaxel.Particle size analyzer, UV-Vis spectrophotometer, FTIR, and XRD were used in the present study to characterize NAT and Doxorubicin encapsulated AuNPs. To check the cytotoxic effect of AuNP-NAT and AuNP-doxorubicin on Pac R /MCF-7 stem cells MTT assay was performed. RT-PCR was performed to check the altered expression of ferritinophagy-related genes. The proliferation and migration potential of the cells before and after treatment with the desired drug combinations was evaluated by clonogenic and scratch assays, respectively. Flow cytometry analysis was done to quantify apoptotic bodies and cell cycle arrest. Cellular ROS was determined using DCD-FA staining.NAT and doxorubicin loaded into AuNP showed enhanced stability and induced ferritinophagy in Pac R /MCF-7 stem cells. The obtained results suggest that AuNP-NAT, combined with a low AuNP-Doxorubicin nanoconjugate dose, might be an effective anti-neoplastic drug targeting the necroptosis-autophagy axis, thereby reducing the adverse side-effects induced by the conventional chemotherapeutic drugs.